Cytotoxicity and Mineralization Activity of Calcium Silicate-Based Root Canal Sealers Compared to Conventional Resin-Based Sealer in Human Gingival Fibroblast Cells - Mohammad Shokrzadeh; Farzaneh Sadat Motafeghi; Anahita Lotfizadeh; Mohammad Ghorbani; Azam Haddadi Kohsar (Hindawi Limited, 2023)
Background. Root canal obturation is performed by gutta-percha cones and sealer. Therefore, these materials, specially sealers, must be biocompatible. This study investigated the cytotoxicity and mineralization activity of two calcium silicate-based sealers (Endoseal MTA and Ceraseal) and an epoxy resin-based sealer (AH26). Materials and Methods. In this experiment, the cytotoxicity of Endoseal MTA, Ceraseal, and AH26 on human gingival fibroblast cells was examined using Methyl-Thiazol-Tetrazolium assay at time intervals of 24, 48, 72, and 120 hr. The mineralization activity of sealers was evaluated by Alizarin red staining assay. Prism, ver.3, software was used to perform statistical tests. One-way analysis of variance analysis, followed by Tukey's test, was used to determine the group differences. P-values < 0.05 were considered statistically significant. Results. Cytotoxicity of sealers decreased gradually (P<0.0001). AH26 showed the highest level of cytotoxicity (P<0.001). In terms of cytotoxicity, no considerable differences were observed between the two-calcium silicate-based sealers (P>0.05). AH26 showed the lowest mineralization activity (P<0.0001). Among the calcium silicate-based sealers, mineralization and formation of calcium nodules were more frequently observed in the Endoseal MTA group (P<0.001). Conclusion. The examined calcium silicate-based sealers had less cytotoxicity and higher mineralization activity than the resin-based sealer (AH26). There was negligible difference between the cytotoxicity of the two-calcium silicate-based, but the cell mineralization caused by Endoseal MTA was higher.